Calendering Machine Performance Analysis to Improve The Smoothness of Batik - S. , Suharno; Alisya Eka Putri; Hermawan Yudha Prasetya; Qodry Al Basyir Amir; Rifki Hikmawan; J. Joemintono (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
This research aims to analyze the performance of the batik ironing machine (calendering) towards ensuring optimal finishing due to the problems associated with the inability to measure the mechanical system of its roll which normally leads to the unevenness of the products. Finishing is an important process in batik production and this is commonly achieved through the calendering machine which is known as one of the mechanical refinements involving a rolling process conducted using high temperatures and pressures to produce fabric products with a flat, smooth, and shiny surface and also create a smooth, moire, and an embossed effect. It is, however, important to note that operators in the batik industry are currently being faced with the problems of finishing and this means there is a need for the appropriate tool for refinement of the fabric. Therefore, this observational study was conducted with the focus on identifying the main components and calculating the mechanical strength of the calendering machine in the batik industry. This involved using the solid work software and the results showed that the calendering machine generally consists of five rolls divided into three metal and two soft rolls. The metal roll has a smooth surface with a hole in the middle for heating which implies it functions as the ironing tool while the soft roll serves as a pressure booster during the ironing process. Moreover, the analysis of structural mechanics showed that the machine has the ability to iron 3.53 meters of fabric in 1 minute. It was also observed that it has six main parts which are the preparation, roller calendar, engine frame, transmission system, boiler engine, and special cooling. The machine was able to produce a batik fabric with a flat, smooth, and shiny surface, thereby, increasing its quality